If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + -8) = 5(6 + c) Reorder the terms: 6(-8 + c) = 5(6 + c) (-8 * 6 + c * 6) = 5(6 + c) (-48 + 6c) = 5(6 + c) -48 + 6c = (6 * 5 + c * 5) -48 + 6c = (30 + 5c) Solving -48 + 6c = 30 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. -48 + 6c + -5c = 30 + 5c + -5c Combine like terms: 6c + -5c = 1c -48 + 1c = 30 + 5c + -5c Combine like terms: 5c + -5c = 0 -48 + 1c = 30 + 0 -48 + 1c = 30 Add '48' to each side of the equation. -48 + 48 + 1c = 30 + 48 Combine like terms: -48 + 48 = 0 0 + 1c = 30 + 48 1c = 30 + 48 Combine like terms: 30 + 48 = 78 1c = 78 Divide each side by '1'. c = 78 Simplifying c = 78
| (8x^2-12x-16)/(2x+1) | | -16+2x=4x+(16+12) | | 3/4t=-2/3 | | -14x-12x=160 | | x/3=36 | | -4+3x=4x | | (x-2)+14=0 | | 5/2(n)=98-n | | 3x-9=4(x-3)+2x | | 2/3=k+1/3 | | 8(x+7)=40 | | (x+3)=(x+2) | | 2x+12-7x=16-13x+8x-4 | | -5(2t-5)+3t=2t-9 | | 4x^5-x^3+7x^2-2=0 | | x/5-x/2=3+3x/10 | | -17.5=7d | | 2y+6=x | | 5x-5=25-3x+6 | | 10x-8+3x-4=9x-4+3 | | 45+x+2x+0.5x=150 | | x+9x=2 | | 1/2(5t-9)=t+9/4 | | (Z+3)=(z+3) | | 4(x-4)=2(x-5) | | (5^2-5)/(4^2+8-7x2) | | 7x-4=6x+3 | | 2x+x=93 | | 4x+2(x+15)=90 | | 500=y | | 120-3/4(y)=60 | | 46=2(2w-5)+2w |